Relação entre profundidade e propriedade de um solo orgânico de Aracruz, Espírito Santo - Lang Otto, Sérgio Renato; Torres Loureiro, Blanor; Ferreira, Paulo Afonso; Fernandes, Bairon; Cecon, Paulo Roberto (Revista Ceres, 2025)
Satured hydraulic conductivity was determined using the auger-hole method with and without hole lining and the piezometer method on 25 areas of one meter of radius, 125 disturbed samples and 125 undisturbed samples (25 areas at 5 depths) of an organic soil were collected at Aracruz, ES — Brazil. razil.